Biological and chemical control of Fusarium wilt fungus on two tomato cultivars - Buhidma, Mohammed S.; Abogharsa, I.A.; Saeed , M.A. (Al-Mukhtar Journal of Sciences, 2007)
The aim of this current study was to investigate the effect of biological and chemical control on degree of infection and percentage of wilt disease of Fusarium wilt (Fusarium oxysporum f. sp. lycopersici) on two tomato cultivars (Marco & Plaza). The effect of biological and chemical treatments were estimated by Winze's equation and indicated that the degree of fungal infection was vary among treatments and between cultivars. The degree of infection in the non-treated plants was increased by 72.0 and 73.6%, while in the treated ones was reduced to 24.4% and 2.1% in both cultivars Marco and Plaza respectively after 49 days from inoculation. The percentage of wilt disease on Marco cv was 1.27 (Fungicide treat). followed by 1.33 (Garlic treat). But they were different on Plaza cv, the most effective one was Fungicide treat. (1.31) followed by Garlic treat. (1.43).